(untitled) (Global Scientific Review, 2026)
This article provides a systematic analysis of the role of the Amu Darya (Oxus/Jayhun) basin in international economic and cultural relations during the ancient and medieval periods. The research is based on data from ancient authors (Strabo, Arrian), Arab geographers (Al-Istakhri, Ibn Hawqal), and encyclopedic scholars such as Abu Rayhan Biruni. The article highlights the importance of strategic crossings such as Amul, Kelif, Shurob, and Chushkaguzar within the Great Silk Road system. The author scientifically substantiates the river’s function not merely as a natural border, but as a transregional economic bridge